Aide Memoire: high level guidance to 2030 for genetic innovation implementation in CWANA++ - Bassi, Filippo (2023)
ICARDA-NARES consultation meeting, 13th-15th December 2022 Istanbul, Türkiye Aide Memoire: high level guidance to 2030 for genetic innovation implementation in CWANA++